Relationship Between Dental Caries and Erosive Tooth Wear in Adolescents - Weber, Megan L.; Søvik, Jenny Bogstad; Mulic, Aida; Deeley, Kathleen; Modesto, Adriana; Tveit, Anne B.; Vieira, Alexandre R. (Frontiers in Dental Medicine, 2022)
Background: Our aim was to investigate the relationship between caries experience and erosive tooth wear of adolescents. Methods: We compared dmft/DMFT data of 795 adolescents to their erosive tooth wear scores using diet as covariate and determined if dental caries and erosive tooth wear scores are associated using linear regression analysis. Diet data and oral hygiene habits were collected using self-reported surveys and erosive tooth wear scores were previously collected. We also compared patients’ genotypes and phenotypes and looked for association between erosive tooth wear experience and different SNPs. A Bonferroni correction was implemented to correct for multiple comparisons. Two-group comparisons were made depending on the phenotype definitions implemented, and both chi-square and linear regression analyses were used to test for association between genetic variants and caries definitions. All covariates were included in each model. Results: For four SNPs (rs17159702, rs10246939, rs1800972, rs1676303), there was an association between a spike in caries experience of DMFT 4 or more between two time points and increased frequency of fruit juice intake. A fifth SNP rs2860216 was shown to be a protective factor toward a spike in caries when coupled with more frequently eating yogurt. We did not find significant associations between our dental caries phenotypes or our demographic data and erosive tooth wear status in our linear regression. Conclusions: Dental caries and erosive tooth wear are two diseases that differ in mechanism and heritability.